Upaya Melestarikan Permainan Tradisional Engklek melalui Teknologi Digital Interaktif - Noor Hasyim; Ati Bahiyati Utami Putri (JURNAL RUPA, 2017)
Traditional games which involved fine motor skill are becoming obsolete nowadays, one of them is engklek. In addition to technological developments, the increasingly diminishing playgrounds and the growing individuality of the urban community has made traditional games much more forgotten. The preservation of engklek needs to be done through a contemporary approach involving recent technologies, one of them is using video games. Video games has potential to grow children's curiosity towards some knowledge that become increasingly rare. The aim of digitization of englek is to introduce traditional games in order to preserve the culture of traditional game for Indonesian children, especially for those whom live in urban areas today. The final result of this design process is an Android game application called PERON Engklek that would introduce traditional games through digital technology for children nowadays. By doing so, it would motivate them to play with their friends.